'You are essentially forced into being an activist': the interplay between Islamophobia and Muslims' civic engagement in Australia. Issue 1 (1st January 2021) - Peucker, Mario
ABSTRACT: Personal and collective experiences of Islamophobia have complex implications for Muslim communities and affect individuals' social positioning, identity, and their (active) citizenship. While some Muslims respond by refraining from civic or political engagement, there is growing empirical evidence that Islamophobia encourages others to become more active. This article synthesises existing research on this under-explored topic and, drawing on a recently concluded study on Muslim intra-community engagement in Australia, presents fresh insights into the complex and multifaceted interplay between Islamophobia and the way in which Muslims enact their citizenship, in particular within a Muslim community context. The findings highlight that Australian Muslims' intra-community volunteering is often driven by their motivation to tackle anti-Muslim stereotypes or to empower fellow Muslims and communities to respond to Islamophobia. Moreover, the study findings suggest the persistence of barriers, from cultural inappropriateness to racism, within non-Muslim civil society groups and pinpoint that Muslims' intra-community engagement may have negative effects on their employment prospects due to discriminatory recruitment decisions.